2019
DOI: 10.1021/acsearthspacechem.9b00054
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Impact of Bacteria on the Aqueous Atmospheric Chemistry of Small Organic Compounds

Abstract: In this study, we use a modeling approach to evaluate the potential impact of microbial metabolism on the organic composition of cloud droplets and atmospheric aerosols. Microbial consumption rates for small organic molecules typically found in cloud and aerosol water were incorporated into a 0-D multiphase photochemical atmospheric chemistry model. We then use the model to simulate the evolution of the organic content of individual cloud and aerosol particles, along with the atmospheric gas phase. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 63 publications
1
16
1
Order By: Relevance
“…While phenol is not a major contributor to the WSOC content in cloud water (5-95 nM ) (Jaber et al, 2020) as compared to 10µm (Ervens et al, 2003b) (Löflund et al, 2002) (Sun et al, 2016) for formic and acetic acids respectively, its degradation processes in the atmosphere might be of interest due to its toxic properties. Overall, our results are in agreement with previous findings that neither chemical processes nor biodegradation are major WSOC 530 losses as compared to deposition (Ervens and Amato, 2020) (Fankhauser et al, 2019). However, in order to comprehensively describe the loss processes and time scales of organic degradation and residence time scales in the atmosphere, both chemical and biological processes should be considered.…”
Section: For Which Organics Is Biodegradation An Efficient Sink In Thsupporting
confidence: 92%
See 2 more Smart Citations
“…While phenol is not a major contributor to the WSOC content in cloud water (5-95 nM ) (Jaber et al, 2020) as compared to 10µm (Ervens et al, 2003b) (Löflund et al, 2002) (Sun et al, 2016) for formic and acetic acids respectively, its degradation processes in the atmosphere might be of interest due to its toxic properties. Overall, our results are in agreement with previous findings that neither chemical processes nor biodegradation are major WSOC 530 losses as compared to deposition (Ervens and Amato, 2020) (Fankhauser et al, 2019). However, in order to comprehensively describe the loss processes and time scales of organic degradation and residence time scales in the atmosphere, both chemical and biological processes should be considered.…”
Section: For Which Organics Is Biodegradation An Efficient Sink In Thsupporting
confidence: 92%
“…The metabolic activity of bacterial strains identified in cloud water (e.g. Pseudomonas, Sphingomonas) has been investigated in lab studies, and it was shown that they can biodegrade organics (e.g., malonate, succinate, adipate, pimelate, formaldehyde, methanol, acetate, formate, phenol and catechol (Delort et al, 2010) (Vaïtilingom et al, 2010(Vaïtilingom et al, , 2011(Vaïtilingom et al, , 2013 (Amato et al, 2007a) (Ariya et al, 2002) (Husárová et al, 2011) (Fankhauser et al, 2019) (Jaber et al, 2020). Based on comparisons of experimentally derived 60 biodegradation rates to chemical rates of oxidation reactions by radicals (e.g., OH, NO3) in the aqueous phase, it was concluded that they might be similar under some conditions, and that, depending on the abundance and metabolic activity of bacteria strains, oxidation and biodegradation processes of organics may compete in clouds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of biodegradation of CCN-derived compounds is limited by the number fraction of cloud droplets that contain bacteria. Malonate / malonic acid and succinate / succinic acid contribute on average to < 5 % to the total organic aerosol mass in ambient particles, e.g., Fu et al (2013) and Kawamura and Ikushima (1993). Their loss by chemical and biological processes will not affect the total carbon budget to a large extent nor the budget of the individual compounds.…”
Section: Ccn-derived Compoundsmentioning
confidence: 99%
“…CC BY 4.0 License. et al, 2002;Fankhauser et al, 2019;Husárová et al, 2011;Vaïtilingom et al, 2010Vaïtilingom et al, , 2011Vaïtilingom et al, , 2013 have been measured in laboratory experiments. Comparison of such rates to those of chemical radical ( • OH 65 or NO3 • ) reactions in the aqueous phase show comparable rates of chemical and microbial processes under atmospherically relevant conditions.…”
mentioning
confidence: 99%